2013
DOI: 10.1128/aac.00282-13
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Retapamulin against Staphylococcus aureus Resistant to Various Antimicrobial Agents

Abstract: Retapamulin and six other antimicrobial agents were evaluated against 155 methicillin-resistant Staphylococcus aureus (MRSA) isolates, including strains resistant to vancomycin, linezolid, daptomycin, and mupirocin by microdilution tests. Time-kill assays were performed against representative MRSA, vancomycin-intermediate S. aureus (VISA), and vancomycin-resistant S. aureus (VRSA) isolates. Retapamulin and mupirocin demonstrated MIC 90 s of 0.12 g/ml and 8 g/ml, respectively, with resistance seen in 2.6% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 6 publications
(6 reference statements)
1
16
2
Order By: Relevance
“…There is very little published data on retapamulin resistance in S. aureus. Retapamulin resistance among mupirocin-resistant S. aureus has been previously shown to be Ͻ1% in the United Kingdom (15) and 2.6% among a general sample of MRSA in the United States (16). This is the first study in a pediatric population to investigate retapamulin resistance, finding a rate of 9.5% among S. aureus isolates causing SSTI, and it was more common among patients with recurrent infections.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…There is very little published data on retapamulin resistance in S. aureus. Retapamulin resistance among mupirocin-resistant S. aureus has been previously shown to be Ͻ1% in the United Kingdom (15) and 2.6% among a general sample of MRSA in the United States (16). This is the first study in a pediatric population to investigate retapamulin resistance, finding a rate of 9.5% among S. aureus isolates causing SSTI, and it was more common among patients with recurrent infections.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have documented cross-resistance between linezolid and pleuromutilins (14). In a survey of MRSA clinical isolates, Saravolatz et al (16) noted that retapamulin resistance was found only in isolates with concomitant linezolid resistance. In addition, the current study revealed a trend for retapamulin-resistant isolates to exhibit cross-resistance with mupirocin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates chosen had previously determined MICs that ranged from 2 to 4 μ g ml −1 for LTX‐109 and 0·06 μ g ml −1 to more than 512 μ g ml −1 for mupirocin (Saravolatz et al . , ). The staphylococcal cassette chromosome mec typing of this group included six type II, three type IVa and one type IV.…”
Section: Methodsmentioning
confidence: 99%
“…At present, retapamulin is approved for treatment of impetigo due to MSSA or Streptococcus pyogenes . Retapamulin has demonstrated activity against S. aureus strains exhibiting resistance to methicillin and mupirocin as well as several other systemic antibiotics [162, 163, 166]. A Phase I/IIa randomized, double-blind, placebo-controlled trial evaluated 3- and 5-day regimens of retapamulin (1%) ointment applied to the anterior nares twice daily in patients persistently colonized with S. aureus .…”
Section: Prevention Strategies: Decolonizationmentioning
confidence: 99%